Organizational performance: influence of contingency factors in Santa Catarina software development companies - Petry, David Rodrigo; Oro, Ieda Margarete; Suzana, Jaqueline; Lorentz, Josiane Aparecida; Piekas, Andrezza Aparecida Saraiva; Paludo, Jorge Carlos (Revista de Administração da UFSM, 2020)
This study assesses the influence of contingency factors such as environment, structure, strategy, technology, and size on the organizational performance of software development companies in the state of Santa Catarina. After the presentation of the foundations that formed the basis for the elaboration of the research construct, there was a quantitative survey that used a structured questionnaire to sample 34 companies in the software industry. For the data analysis, we used statistical instruments, reliability tests, the Pearson correlation and regressions to achieve the proposed objectives. The results show that, in general, the contingency factors influence the performance of software companies. After individually comparing the contingency factors with performance, the only factor that showed no significant correlation was structure while all the other factors were correlated with performance. In the regression, the generated model retained only the variable strategy and excluded the others. This established a regression equation that provided the degree of influence of this variable on the performance of software companies.